2020
DOI: 10.1038/s41598-020-58522-5
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic-di-GMP signalling network regulates biofilm formation and surface associated motility of Acinetobacter baumannii 17978

Abstract: Acinetobacter baumannii has emerged as an increasing multidrug-resistant threat in hospitals and a common opportunistic nosocomial pathogen worldwide. However, molecular details of the pathogenesis and physiology of this bacterium largely remain to be elucidated. Here we identify and characterize the c-di-GMP signalling network and assess its role in biofilm formation and surface associated motility. Bioinformatic analysis revealed eleven candidate genes for c-di-GMP metabolizing proteins (GGDEF/EAL domain pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…Analysis of biofilm formation also revealed that isolates derived from patient blood samples formed significantly more biofilm than isolates from sputum or bronchial wash, or isolates from wound samples. Both biofilm and motility phenotypes have been shown to vary widely across clinically isolated strains of A. baumannii [ 23 ] and both processes have both been shown to be regulated by overlapping signaling networks in this pathogen [ 24 , 25 ]. Although biofilm and motility phenotypes varied widely across strains in our study as well, we observed an inverse relationship between motility and biofilm formation in the 17 clinical isolates examined.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of biofilm formation also revealed that isolates derived from patient blood samples formed significantly more biofilm than isolates from sputum or bronchial wash, or isolates from wound samples. Both biofilm and motility phenotypes have been shown to vary widely across clinically isolated strains of A. baumannii [ 23 ] and both processes have both been shown to be regulated by overlapping signaling networks in this pathogen [ 24 , 25 ]. Although biofilm and motility phenotypes varied widely across strains in our study as well, we observed an inverse relationship between motility and biofilm formation in the 17 clinical isolates examined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to twitching motility, some isolates of A. baumannii move on living and non-living surfaces without relying on flagella by another mode of motility called surface-associated motility [97]. This type of motility also requires type IV pili, quorum sensing, lipo-oligosaccahride production, and 1,3-diaminopropane, which mediates signaling needed for impacting surface-associated motility by quorum sensing [90].…”
Section: Motilitymentioning
confidence: 99%
“…Most c-di-GMP-dependent signalling pathways regulate the bacteria ability to interact with abiotic surfaces or with other bacterial and eukaryotic cells. Eleven genes for GGDEF/EAL proteins in the genome of the A. baumannii 17 , 978 strain were identified, and most of the predicted proteins were enzymatically active [ 118 ]. It was demonstrated that distinct panels of these enzymes promote biofilm formation, macro-colony growth, and surface-associated motility [ 118 ].…”
Section: Biofilm and Heterogeneity Of A Baumanniimentioning
confidence: 99%
“…cAMP inhibits pellicle formation [ 104 ]. The synthesis of Csu pili depends on cyclic di-GMP (c-di-GMP) [ 118 ] and the BfmRS and GacSA systems [ 48 , 119 , 120 ]. The hybrid two-component regulator CheA/Y controls the expression of Csu pili and acinetin-505 via QS [ 106 , 121 ].…”
Section: Figurementioning
confidence: 99%